Distal Biceps Repair With Flexible Instrumentation and Risk of Posterior Interosseous Nerve Injury: A Cadaveric Analysis. Issue 11 (22nd November 2018) - Tat, Jimmy; Hart, Adam; Cota, Adam; Alsheikh, Khalid; Behrends, Dominique; Martineau, Paul A.
Background: Current repair techniques using cortical button fixation cannot achieve anatomic reconstruction of the distal biceps when performed through a single-incision anterior approach. We recently introduced a single-incision technique that uses flexible guide pins and flexible reamers to allow for an insertion point on the tuberosity that more closely approximates the anatomic footprint of the distal biceps. Purpose: To investigate the safety of this technique with regard to nerve injury by comparing the guide pin position relative to the posterior interosseous nerve in 16 cadaveric elbows through use of a flexible versus rigid reamer. Study Design: Descriptive laboratory study. Methods: A standard single-incision anterior approach was performed in all cadaveric specimens, and the biceps tendon was dissected off the tuberosity. In 8 specimens, a traditional straight guide pin was used with a cortical button repair inserted through the bicipital tuberosity as close to the anatomic tendon footprint as possible. In the remaining 8 specimens, a curved guide was used to insert a flexible guide wire through the tuberosity within the native footprint. Dissection was carried out to measure the distance from the exit point of the guide pin to the posterior interosseous nerve. The 2 groups were compared by use of nonparametric Wilcoxon rank-sum test (significance threshold, P < .05). Results: The mean distance of the guide wire to the posterior interosseous nerve was 11.6 mm (SD, 3.4 mm; range, 6.5-16.9 mm) in the standard rigid instrument group compared with 8.6 mm (SD, 4.2 mm; range, 1.0-13.9 mm) in the flexible instrumentation group; the difference between groups was not statistically different ( P = .19; 95% CI, –1.1 to 7.1). Conclusion: Based on our cadaveric testing, the use of flexible instrumentation in a single-incision repair of the distal biceps presents with no significant difference in risk of damage to the posterior interosseous nerve compared with standard rigid instruments. In view of the relatively small number of specimens, however, some caution should be observed when applying these results clinically. Clinical Relevance: As contemporary techniques in sports medicine strive to re-create each patient's native anatomic characteristics, the use of flexible instruments allows for a more anatomic repair of the distal biceps, and our study demonstrates that it is a safe option. The next step is to evaluate its safety in vivo.